Energy Security Concept in Russia and South Korea - Dooyum, Uyeh Daniel; Mikhaylov, Alexey; Varyash, Igor (International Journal of Energy Economics and Policy, 2020)
One of the key problems hindering the strengthening of cooperation between South Korea and the Russian Federation not only in the energy sector, but also in other areas, is a negative impact in a kind of historical memory of previous experience of cooperation, or rather failure in implementation of projects or lack of implementation in general. Many projects in potentially promising areas remain on paper. Projects have never been implemented include modernization and commissioning by a joint Russian-North Korean enterprise with the participation of Russian Railways of the railway section from the Khasan station (Russia) to the port Rajin in order to transit from South Korea and gain access states of the Korean Peninsula to the Trans-Siberian Railway. Keywords: Energy Sources, South Korea Energy Policy, Resource Saving, Economic Development, Energy Cooperation. JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.9116